Pengaruh Word Of Mouth, Kualitas Pelayanan Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Lims Cafe Kota Tebing Tinggi - Arif, Nanda Aulia; Fitrianingsih, Fitrianingsih (Digital Business Progress, 2024)
This research aims to analyze the influence of word of mouth variables, service quality and product quality on purchasing decisions at Lims Cafe, Tebing Tinggi City. This research is a quantitative research with 96 respondents. Data analysis using SPSS software with the results of this research showing partial hypothesis test results for each variable, namely word of mouth, service quality and product quality on purchasing decisions at Lims Cafe, Tebing City. Meanwhile, the simultaneous test results show word of mouth, service quality and product quality simultaneously influence purchasing decisions at Lims Cafe, Tebing Tinggi City.